Piptochaetium fuscum (Nees ex Steud.) Barkworth, Ciald., & Gandhi, a new combination replacing Piptochaetium setosum (Trin.) Arechav. - Barkworth, Mary E. (2014)
A new name, Piptochaetium fuscum, is provided for a taxon hitherto known as Piptochaetium setosum (Trin.) Arechav. Morphological, anatomical, and molecular studies that argue against including Piptochaetium in Stipa, and hence use of S. purpurata (Phil.) Columbus & J.P. Sm., are cited.